CONTEXT-BASED INDONESIAN LANGUAGE LEARNING FOR LITERACY ERADICATION AND LITERACY IMPROVEMENT IN KOKODA VILLAGE, PAPUA - Hikmah, Nur Hikmah; Alam, Risma; Nur, Liesa Novia; Yulianingsih, Lilik; Belyanan, Martha Elinna (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The low proficiency in the Indonesian language among residents of Kokoda Village serves as the primary background for this study, which is influenced by limited access to formal education and the complex socio-cultural context of the community. This research aims to measure the improvement in participants’ Indonesian language skills after engaging in a learning program designed with a contextual and participatory approach, as well as to understand the level of participant engagement throughout the program implementation. A quantitative descriptive method was employed, involving 45 participants as research subjects. Data were collected through tests assessing writing, reading, and speaking abilities in Indonesian. Data analysis was conducted in three stages: data processing, data management, and result interpretation, to provide a comprehensive overview of participants’ skill development. The findings reveal significant improvements across all language skill areas: reading ability increased to an average of 72%, writing ability reached 80%, and speaking ability reached 69%. Additionally, participant engagement was high, with 84% consistently attending at least 75% of the learning sessions, indicating strong motivation fostered through an interactive learning approach that integrates local content. The study’s implications highlight the importance of implementing learning programs that are sensitive to socio-cultural contexts and empower local facilitators to enhance functional literacy in remote areas. This approach not only improves learning outcomes but also supports program sustainability by strengthening social and cultural bonds within the community. The research provides recommendations for the development of more responsive educational programs that address the specific needs and characteristics of indigenous communities in future initiatives